TINJAUAN DAN KOMPARASI DESAIN MINUMAN KEKINIAN DENGAN PENDEKATAN SENSORY BRANDING - Aryani, Dewi Isma (Jurnal Studi Komunikasi dan Media, 2024)
Franchising industry for contemporary beverage products, innovative branding is done utilizing sensory branding as a component of marketing, together with creativity and the use of appropriate design psychology as a difference. Contemporary beverage design is essential for producing aesthetic appeal and sensory experiences. Through the use of materials, color schemes, lighting, product and window displays, and sensory-branded store interiors, consumers are provided emotional experiences. The primary senses that will be explored in this research on sensory branding are sight and touch. Design psychology is meanwhile researched based on customer perceptions and patterns of human social interaction. In this study, contemporary beverage designs from several well-known companies will be analyzed and contrasted according to the sensory branding components used by seven popular contemporary beverage brands. Descriptive qualitative case studies are the research methodology employed. Consequently, by exposing sensory branding findings and design psychology elements from contemporary beverage franchises, particularly those relating to the image of store interior branding, style and design elements, as well as visual merchandising as a form of design recommendation, the results of this study will provide deeper insight into how contemporary beverage design can influence consumer preferences and their purchasing decisions.